An investigation into the causes of learners’ negative attitudes towards History at Secondary School level in Mount Darwin District Rural Schools. - Mukwesha, Ropafadzo (Midlands State University, 2020)
The study sought to examine the causes of learners’ negative attitudes towards History at Secondary School level in Mount Darwin District Rural Schools. The study also offers the ways that can be used to improve learners’ attitudes. Mount Darwin District has 47 Secondary Schools. For the purpose of this study the researcher focused on 3 rural schools only. The researcher used a sample of 45 learners, 15 teachers and 3 Heads of Departments’ .The descriptive survey research design was used to gather pertinent information. Questionnaires for pupils and teachers and interviews for History head of departments were used to gather relevant data for the study. The researcher used Purposive sampling to select the schools .Simple random sampling was used in the selection of teachers and pupils. From the study it materialized that learners’ in Mount Darwin District rural schools develops negative attitudes due to the way the subject is taught, shortage of History material resources, the influence of parents and guardians, teacher attitudes, introduction of STEM and the introduction of the New Curriculum. Nevertheless, the researcher also concluded that even though learners developed negative attitudes towards History at Secondary level, they can be stimulated by effectively equipping the schools with enough History material resources, making use of the interactive methodologies and empowering the parents or guardians on the value of History in their pupil’s lives. The researcher recommended that the teachers should always avoid expository methods of teaching History and that carrier guidance should be given to the students at an earlier stage.